Glia as a key factor in cell volume regulation processes of the central nervous system - Ochoa-de la Paz, Lenin David; Gulias-Cañizo, Rosario (Frontiers in Cellular Neuroscience, 2022)
Brain edema is a pathological condition with potentially fatal consequences, related to cerebral injuries such as ischemia, chronic renal failure, uremia, and diabetes, among others. Under these pathological states, the cell volume control processes are fully compromised, because brain cells are unable to regulate the movement of water, mainly regulated by osmotic gradients. The processes involved in cell volume regulation are homeostatic mechanisms that depend on the mobilization of osmolytes (ions, organic molecules, and polyols) in the necessary direction to counteract changes in osmolyte concentration in response to water movement. The expression and coordinated function of proteins related to the cell volume regulation process, such as water channels, ion channels, and other cotransport systems in the glial cells, and considering the glial cell proportion compared to neuronal cells, leads to consider the astroglial network the main regulatory unit for water homeostasis in the central nervous system. In the last decade, several studies highlighted the pivotal role of glia in the cell volume regulation process and water homeostasis in the brain, including the retina; any malfunction of this astroglial network generates a lack of the ability to regulate the osmotic changes and water movements and consequently exacerbates the pathological condition.